2007
DOI: 10.2987/8756-971x(2007)23[164:drbfco]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Developing Recombinant Bacteria for Control of Mosquito Larvae

Abstract: Genetic engineering techniques have been used to significantly improve mosquito larvicides based on the bacteria Bacillus thuringiensis (Bt) subsp. israelensis (Bti) and Bacillus sphaericus (Bs). These new larvicides hold excellent promise for providing better and more cost-effective control of nuisance mosquitoes and vectors of important diseases, including the anopheline vectors of malaria and culicine vectors responsible for filariasis and viral encephalitides. The toxicity of Bti and Bs is due primarily to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 45 publications
0
48
0
2
Order By: Relevance
“…Our data imply an interaction between the Cry48Aa and Cry49Aa components that results in a complex and specific combination of cytopathological effects resulting from the joint action of Bin and three-domain-protein-like insecticidal proteins. It has been demonstrated that resistance selection is inversely proportional to the number of toxins used, particularly those that interact with distinct receptors on midgut epithelial cells (11,12,28). The ability of Cry48Aa/Cry49Aa to overcome resistance makes this toxin a promising weapon in the armory of safe, insecticidal proteins with great potential for use as active ingredients of a new generation of biolarvicides for vector control that conjugate toxic factors with distinct sites of action.…”
Section: Discussionmentioning
confidence: 99%
“…Our data imply an interaction between the Cry48Aa and Cry49Aa components that results in a complex and specific combination of cytopathological effects resulting from the joint action of Bin and three-domain-protein-like insecticidal proteins. It has been demonstrated that resistance selection is inversely proportional to the number of toxins used, particularly those that interact with distinct receptors on midgut epithelial cells (11,12,28). The ability of Cry48Aa/Cry49Aa to overcome resistance makes this toxin a promising weapon in the armory of safe, insecticidal proteins with great potential for use as active ingredients of a new generation of biolarvicides for vector control that conjugate toxic factors with distinct sites of action.…”
Section: Discussionmentioning
confidence: 99%
“…As an increasing number of recombinant B. thuringiensis strains containing Cyt toxins are developed with the goal of obtaining a more efficient insecticidal product than B. thuringiensis subsp. israelensis (14,15), it is necessary to better characterize the fate of Cyt toxins in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that the interest in alternative nonchemical strategies has increased in recent years. The use of biological control agents such as bacteria, protozoa, nematodes, and fungi has accordingly been developed with an attempt at gaining control over mosquito populations (Federici et al 2007). …”
Section: Introductionmentioning
confidence: 99%